A novel HYLS1 homozygous mutation in living siblings with Joubert syndrome. Issue 6 (4th March 2016) - Oka, M.; Shimojima, K.; Yamamoto, T.; Hanaoka, Y.; Sato, S.; Yasuhara, T.; Yoshinaga, H.; Kobayashi, K.
Abstract : The p.Asp211Gly homozygous HYLS1 mutation is so far known to cause only hydrolethalus syndrome, a lethal malformation syndrome. We report living sibling patients with a homozygous no‐stop mutation in exon 4 of HYLS1, NM_145014.2:c.900A>C (p.Ter300TyrextTer11) in the second decade of life. The proband has Joubert syndrome (JS). The younger brother also has JS and an enlarged posterior fossa that was initially diagnosed as Dandy–Walker malformation. The present mutation is unique as it affects the stop codon. The product protein HYLS1 plays an essential role in the formation of the primary cilium. This report provides insight into the spectrum of disorders involving midline brain defects closely related to cilium dysfunction or ciliopathy. Abstract :